Quality Analysis Of Antenatal Care Services During The Covid-19 Pandemic - St Salma Dodal; Sri Dinengsih; Jenny Anna Siauta (Universitas Islam Lamongan, 2021)
Antenatal Care is a pregnancy service that aims to improve the physical and mental health of pregnant women optimally, so that they are able to face the period of childbirth, postpartum, newborn, and family planning. In this COVID-19 pandemic situation, there are many restrictions on almost all routine services including maternal and newborn health services. The more complete the Antenatal Care services provided, the better the service quality and satisfaction for pregnant women. To determine the relationship between direct evidence, reliability, responsiveness, assurance and empathy to the quality of ANC services in the work area of the Wolo Health Center in 2020. This research is a quantitative analytic study with an analytical survey design. The sample in this study were pregnant women with TM II and III in the working area of the Wolo District Health Center. Kolaka in 2020 as many as 86 people for the purposes of sampling. Data were analyzed using testChi Square.Research Results: There is a significant relationship between physical evidence, reliability, responsiveness, assurance and empathy on the quality of antenatal care services in the Work Area of the Wolo District Health Center. Kolaka Year 2020. There is a significant relationship between direct evidence, reliability, responsiveness, assurance and empathy on the quality of antenatal care services. Improve the quality of ANC services during the Covid 19 Pandemic, such as adding land for indoor needs which must be spacious, so that pregnant women TM II and III feel comfortable in the waiting room for health services with a minimum distance of 1 meter.